Outcomes of two surgical techniques using silicone rod for frontalis sling suspension to treat severe ptosis - Galindo-Ferreiro, Alicia; Akaishi, Patricia; Hanafi, Somaya; Khandekar, Rajiv; Galvez-Ruiz, Alberto; Schellini, Silvana [UNESP]; Cruz, Augusto (SLACK, 2017)
Purpose: To compare outcomes of two techniques of frontalis silicone sling surgery. Methods: This retrospective, nonrandomized chart review was performed on patients undergoing frontalis sling surgery between 2008 and 2011. Silicone rods were sutured to the tarsal plate through an eyelid crease incision (open method) or stab incisions (closed method). Data were collected on age, gender, type of surgery, preoperative and postoperative margin reflex distance (MRD), and complications. A successful outcome was defined as a postoperative score of 2 to 4 for MRD or an improvement in MRD. Results: A total of 155 eyelids of 146 patients with ptosis were included. There were 60 patients in the open method group and 85 patients in the closed method group, respectively. Successful outcomes were seen in 30 (50%) patients in the open method and 44 (51.8%) patients in the closed method groups. There were 61 (71.8%) patients in the open method group and 45 (75%) patients in the closed method group who had improved MRD at last follow-up. The main complications were exposure keratitis, eyelash ptosis, and eyelid crease abnormalities that occurred only in the closed method group. Conclusions: The silicone frontalis sling procedure had the same success rates in both the open and closed methods. Eyelash and eyelid crease abnormalities were unique to the closed method.